"A Grain of Salt in a Pepper Shaker": Interviewing Whites, Blacks, and Latinos about Their Neighborhood Preferences. Issue 3 (11th May 2016) - Meyerhoffer, Cassi A.
Abstract : Several perspectives dominate as explanations for neighborhood preferences: pure race, racial proxy, race‐based neighborhood stereotyping, and race‐associated neighborhood factors. This analysis extends and supports the pure race and race‐associated neighborhood factors arguments by showing that these theories are applied differently depending on respondents' social class, race and ethnicity, and whether they are talking about white, black, or Latino neighborhoods. Race‐associated factors are emphasized for white and black neighborhoods, but pure race serves as a better theoretical framework for understanding people's preferences for Latino neighborhoods. I analyze qualitative interview data, using maps of real neighborhoods and hypothetical neighborhood show cards, to examine the neighborhood preferences of 65 white, black, and Latino residents in Ogden, Utah, and Buffalo, New York.